Irritant Contact Dermatitis Risk of Common Topical Traditional Chinese Medicines Used for Skin-Lightening: A Pilot Clinical Trial with 30 Volunteers. (10th April 2014) - Tsai, Kao-Sung; Lin, Tzu-Chun; Wu, Meng-Tse; Shen, Jui-Lung; Mao, Ming-Ya; Chen, Huey-Yi; Chen, Yung-Hsiang; Chen, Wen-Chi
Abstract : Topical traditional Chinese medicine- (TTCM-) related contact dermatitis is not uncommon but ignored. Patch and photopatch tests using 6 individual herbal ingredients and Bai-Zhi-Kao (BZK; 白 芷 膏 ), a skin-lightening TTCM preparation, were conducted on 30 participants. Twenty-five subjects showed at least 1 positive reaction, including 6 (20.0%) participants who reacted to BZK. The majority reacted to Radix Ampelopsis japonica (Bai-Lian; 白 蘞 ) (60.0%), whereas few reacted to Rhizoma Bletilla striata (Bai-Ji; 白 芨 ) (16.7%), Rhizoma Atractylodis macrocephalae (Bai-Zhu; 白 朮 ) (10.0%), Radix Angelicae dahuricae (Bai-Zhi; 白 芷 ) (3.3%), and Herba asari (Xi-Xin; 細 辛 ) (3.3%). In the photopatch test, 3 participants (10.0%) reacted positively to BZK and 10 to ≥1 constituent; however, all reacted to Radix Angelicae dahuricae (26.7%), Radix Ampelopsis japonica (13.3%), and Rhizoma Bletilla striata (3.3%). In contrast, no subjects showed positive reactions to Sclerotium Poria cocos (Bai-Fu-Ling; 白 茯 苓 ). Thus, BZK and its constituents might present potential latent risk of contact dermatitis owing to the possible presence of Radix Ampelopsis japonica and Radix Angelicae dahuricae . Furthermore, TTCMs, particularly cosmetic products, must be used carefully, with ample warning of potential contact dermatitis risk.